2015
DOI: 10.1016/j.envres.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Quantity, composition and water contamination potential of ash produced under different wildfire severities

Abstract: Wildfires frequently threaten water quality through the transfer of eroded ash and soil into rivers and reservoirs. The ability to anticipate risks for water resources from wildfires is fundamental for implementing effective fire preparedness plans and post-fire mitigation measures. Here we present a new approach that allows quantifying the amount and characteristics of ash generated under different wildfire severities and its respective water contamination potential. This approach is applied to a wildfire in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
9
62
1
Order By: Relevance
“…During post-fire floods, streams can deliver bedload (generally coarse sediment), suspended sediment (turbidity) and debris to reservoirs. Post-fire inputs of chemical constituents derived from ash and the underlying soil can lead to long-term effects on water-storage reservoirs [62]. It has been estimated that there are 16.7 million reservoirs globally [63].…”
Section: Introductionmentioning
confidence: 99%
“…During post-fire floods, streams can deliver bedload (generally coarse sediment), suspended sediment (turbidity) and debris to reservoirs. Post-fire inputs of chemical constituents derived from ash and the underlying soil can lead to long-term effects on water-storage reservoirs [62]. It has been estimated that there are 16.7 million reservoirs globally [63].…”
Section: Introductionmentioning
confidence: 99%
“…De la Rosa et al () have suggested that WLs at the refractory pool correspond mainly to charred organic residues, whereas Santín et al () reported that the production of pyrogenic OM has its maximum at temperatures over 600 °C. Several studies have previously suggested a direct impact of ash on soil nutrient content, basing this hypothesis on laboratory or field leaching experiments (Marion et al, ; Molina et al, ; Escudey et al, ) or studies of ash composition (Khanna et al, ; Pereira et al, ; Santín et al, ) and post‐fire soil nutrient content (Khanna & Raison, ; Andreu et al, ; Dorta Almenar et al, ). However, unlike these previous studies, we demonstrate a direct quantitative link between the content of charred organic residues in the soil (represented by the SOM refractory pool) and soil nutrient values using a field approach and samples affected by a wildfire.…”
Section: Discussionmentioning
confidence: 99%
“…The materials were air dried (Bodí, Mataix-Solera, Doerr, & Cerdà, 2011) at room temperature (20 C), mixed, and weighed daily until constant mass was reached. The sampling approach was similar to the method used by Santín, Doerr, Otero, and Chafer (2015) in a wildfire ash and laboratory heating study. Soils were sifted through 6.25-mm mesh to remove rocks and large detritus and then passed through a #20 sieve (0.841 mm).…”
Section: Sampling and Processing Of Soils And Littermentioning
confidence: 99%